The Influence of Customer Experience on Brand Image on Alfagift Application - Fakhira, Najma Nuha Noor; Primasari, Intan (Jurnal Ilmiah Komunikasi Makna, 2024)
Customer experience is vital for brand differentiation and influencing consumer perceptions, with a deep understanding of its impact on brand image being essential for winning over consumers and ensuring success. Customer experience includes interaction with the application, service quality, and ease of use. This study examines the influence of customer experience on brand image in the Alfagift application. A quantitative method was used to collect data through online surveys of 103 Alfagift application users. The data were analyzed using descriptive and verification analysis through Hypothesis Testing (T Test and F Test) and statistical techniques such as linear regression to test the relationship between customer experience and brand image. The analysis results show that brand attitude and behavior received the highest percentage at 71.11%, indicating a positive response from respondents towards the brand image. The main finding of this study is that customer experience has a significant influence on the brand image of the Alfagift application, with a percentage of 74%, while the remaining 26% is caused by other factors, thus H1 can be accepted. This study is expected to provide valuable insights for Alfagift in improving their customer experience and strengthening their brand image in the public eye.